Improving Inventory Management of Organizational and Individual Equipment at Central Issue Facilities - Fan, Carol E. (RAND Corporation, 2013)
Army Central Issue Facilities do not have a formal mechanism signaling when to review inventory levels and when and whether to requisition items. This study provides logistics leaders need a routinized inventory review process to help improve inventory management practices. The current process is based on managers' experience and expert judgment, and, because of local differences, can be executed unevenly and typically infrequently.